Unknown Input Observer Design for Linear Fractional-Order Time-Delay Systems - Boukal, Y.; Darouach, M.; Zasadzinski, M.; Radhy, N.E. (Journal of Applied Nonlinear Dynamics, 2026)
This paper considers unknown input functional fractional order observer design for fractional-order linear time-invariant (LTI) systems with a constant time delay. After given the existence conditions of such observer, based on the fractional order Lyapunov stability approach, a sufficient condition for the asymptotic stability of the estimation error is given in a linear matrix inequality (LMI) formulation. The obtained results are illustrated by a numerical example.